Characteristics of intermediate frequency debris flow and analysis of the hazard of blockage in Hada gully, Weixi County of Yunnan Province - Xianghongshen WANG; Guisheng HU; Zhiquan YANG; Huayong NI (Zhongguo dizhi zaihai yu fangzhi xuebao, 2023)
Intermediate-frequency debris flows has the characteristics of high danger and long outbreak period. Human activities can trigger its occurrence and aggravate its disaster severity. When the channel cannot meet the capacity for drainage and water transport, it will cause blockage and endanger the safety of both sides of the strait and even the main river channel. Due to the lack of analysis on the danger of intermediate-frequency debris flows, this paper takes the intermediate-frequency debris flow in Hada Gully, Yunnan Province as an example to explore its characteristics and the danger of its recurrence and channel blockage caused by debris flows and proposes prevention and control suggestions. The results show that the debris flow has a density of 1.62 t/m3, a flow velocity of 4.794 m/s at the outlet of the channel, a peak flow rate of 54.43 m3/s at the channel outlet and a total discharge of 11072.03 m3 for a single occurrence based on the 10% burst frequency. A culvert was constructed in the downstream channel, with a flow capacity of 16.5 m3/s, which is less than the flow rate of a debris flow once in 20 years. Once a large debris flow occurs, there is a risk of blockage. The study found that the hazard level of intermediate-frequency debris flows in Hada gully is highly dangerous, and the history of blockage indicates the possibility of its recurrence and the risk of debris flow blocking the Lapu River.